Propuesta de Agroturismo para el Centro Binacional de Formación Técnica Zapotepamba Parroquia Casanga de la Provincia de Loja - Rivera Torres, Irvim Daniel (2019)
The present research called Agroturism Proposal for the Zapotepamba Technical Training Binational Center of the Casanga parish of the Province of Loja. It consists of converting the Center into an agro-tourism product, through the fusion of agricultural production, agriculture and tourism. The whose general objective consisted in DESIGNING A PROPOSAL OF AGROTOURISM FOR THE ZAPOTEPAMBA BINATIONAL TECHNICAL TRAINING CENTER OF THE CASANGA PARISH OF THE PROVINCE OF LOJA. we propose the agrotourism activity as a means of local tourism development. In the first objective, it was proposed to carry out the Tourist Diagnostic of the Casanga Parish, of the Province of Loja. For the development of the first objective, the analytical, synthetic, inductive and deductive method is used, starting with the direct observation technique, based on the field study, the Tourist Diagnostic will be developed, using the Carla Ricaurte matrix. The inventory form of tourist attractions of the Ministry of Tourism is used, as a support technique an interview is carried out which will be applied to the Director of the CBFTZ. It was concluded with the analysis of the SWOT and the high impact matrix. In what represents the second Objective: AGROTURISM DEVELOPMENT PROPOSAL FOR THE ZAPOTEPAMBA BINATIONAL TECHNICAL TRAINING CENTER. The field work is carried out, establishing the attractions to be considered, with the help of the GPS, the georeferencing points will be taken to download them and design the proposed activities to be developed. The specifications of the tourism signage for the implementation of the proposal were determined, taking as reference the Tourism Signaling Manual of the Ministry of Tourism, the brand was also designed and the name of the Proposals called "Zapotepamba its look at Agrotourism" was raised. The description of the target client to which our product is intended was also prepared, the forms of commercialization and a table of agro- 5 tourism activities to be carried out and days of permanence in the Center for the development of said activities since they can not be executed by means of of an itinerary or following an established order. For the third objective. SOCIALIZE THE PROPOSAL OF AGROTOURISM TO THE COLLECTIVITY AND AUTHORITIES INVOLVED IN THE ACTIVITY OF THE CENTER. The MARPP technique was used, which was developed in three phases. In the previous phase, the pertinent procedures were carried out to comply with the objective, call and invitations of authorities and those involved in the Center's tourism activity. The second is the Socialization where a socialization agenda was made and the results of the research project were presented. The third Results of the socialization where conclusions and recommendations of the proposal-were-indicated. Finally, the conclusions and recommendations of the thesis work were considered the importance of executing this project as a means of local tourism development. As conclusions, this proposal helped to identify that the center has agricultural and agricultural wealth that should be considered attractive when visiting the Center. Likewise, the participants recommend that other activities that are not practiced in the Center should be included in order to be more identified. To provide a better experience to visitors.